Pengaruh ROA, Ukuran Perusahaan terhadap PER Sektor Basic Materials - Wahyu Aji Nugroho; Faradila Meirisa (MDP Student Conference, 2026)
The purpose of this study is to determine how return on assets (ROA) and company size affect the price-earnings ratio (PER) of basic materials companies listed on the Indonesia Stock Exchange (IDX) from 2022 to 2024. A purposive sampling method was used to select 83 companies from the study population, resulting in a sample of 75 companies. The price-earnings ratio (PER) is partially influenced by company size, as shown by the test results. Conversely, the price-earnings ratio (PER) is significantly and negatively affected by return on assets (ROA). At the same time, the price-earnings ratio (PER) is significantly influenced by company scale and return on assets (ROA).